2022
DOI: 10.47717/turkjsurg.2022.5816
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative scoring system validation and analysis of associated risk factors in predicting difficult laparoscopic cholecystectomy in patients with acute calculous cholecystitis: A prospective observational study

Abstract: Objective: Today laparoscopic cholecystectomy (LC) is the treatment of choice for acute cholecystitis. However, the presence of severe inflammation makes it challenging for the surgeons to accurately recognize the Calot’s triangle which increases the risk of intraoperative complications. The aim of this study was to explore the validity of a scoring system used to predict difficult LC and to analyse the risk factors associated with difficult cholecystectomy in the setting of acute calculous cholecystitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Predicting the severity of acute cholecystitis is important to achieve the best therapeutic outcomes and prevent adverse postoperative events [2,[26][27][28][29]. Local inflammation and surgical trauma induce metabolic and systemic inflammatory responses, which may lead to systemic complications [30]. Understanding and addressing inflammation and the possible systemic imbalances that it may cause is important to prevent adverse outcomes and unnecessarily prolonged hospital stays in cases with AC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Predicting the severity of acute cholecystitis is important to achieve the best therapeutic outcomes and prevent adverse postoperative events [2,[26][27][28][29]. Local inflammation and surgical trauma induce metabolic and systemic inflammatory responses, which may lead to systemic complications [30]. Understanding and addressing inflammation and the possible systemic imbalances that it may cause is important to prevent adverse outcomes and unnecessarily prolonged hospital stays in cases with AC.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used for diagnosis, CT and ultrasound examination may not accurately predict advanced AC [30,31]. In a study on 1115 patients who underwent surgery for acute calculous cholecystitis, Goiayev et al [31] found that even in cases with a gallbladder wall of ≤ 4.85 mm, if the NLR > 5.65 and the total leukocytes exceed 8100/mm 3 , there is a 92% probability of complicated AC, including gangrenous, perforated, emphysematous, or necrotizing AC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 The complexity of LC is influenced by multiple patientrelated factors, including but not limited to, the history of previous abdominal surgeries, the patient's body mass index (BMI), the presence of acute or chronic inflammation, and specific gallbladder (GB) anatomical variations. 4 These factors can increase the risk of complications such as bile duct injury (BDI) or the need for conversion to OC, impacting the patient's recovery trajectory and overall outcome. 5 Given this context, there has been significant interest in developing pre-operative scoring systems to categorize the anticipated difficulty of LC.…”
Section: Introductionmentioning
confidence: 99%